From principles to practice, indigenous peoples and biodiversity conservation in Latin America / Andrew Gray, Alejandro Parellada, Hellen Newing - Gray, Andrew [et.al] (Perú: International Work Group for Indegenous Affairs, 1998)
El Sira communal reserve, the Pacaya-Samiria National reserve, the tambopata-candamo reserve; the western Amazon, Cuyabeno wildlife production reserve, Colombia, yaigoje indigenous resguardo nacional reserve; the northern Amazon and the Orinoco Basin, Venezuela, the upper Orinoco-casiquiare biosphere reserve, analytical notes on the management, Brazil the case of raposa Do Sul; the gran chaco region, the kaa-iya protected are of the grn chaco a case of collaboration between indigenous peogles and conservationists; central america, the tawahka asagni biosphere reserve in the context of ecological isues in Honduras, Costa Rica, the cases of Talamanca and Maleku.
Contents, list of participants
Col. Soc
Keywords: 1. CONSERVATION AND PROTECTION 2. INDEGENOUS-PEOPLES AND BIODIVERSITY CONSERVATION 3. NATURAL RESOURCES 4. AGROFORESTRY